Challenging traditions: Systematic review of practice, instruction, and motor skill acquisition in soccer - Pacheco, M. M.; De Oliveira, L. M. M.; Dos Santos, C. C. A.; Filho, J. R. M. G.; Drews, R. (International Journal of Sports Science & Coaching, 2023)
Williams and Hodges (2005) stated five myths that soccer coaches held when organizing their athletes` practice. However, their arguments were based, majorly, in laboratory studies which limit their validity. Here, we performed a systematic review to verify the validity of their claims and map the current scenario of how coaches can manipulate factors of practice (augmented information, focus of attention, demonstration, and practice schedule) to support learning and performance in soccer. The results, in terms of each category or the myths presented, are, in most cases, not unanimous and much more must be performed to support, or criticize, coaches` practice. We provide an encompassing view that provides general ideas for practice and future research.